Mechanisms for Increasing the Economic and Organizational Efficiency of the Management of the Medical Service Sector (Texas Journal of Medical Science, 2023)
The medical service sector is one of the most important and rapidly growing sectors globally. However, the efficient management of this sector faces various challenges, including limited resources, increasing costs, and rising demand for healthcare services.